Evaluación de fincas ganaderas mediante indicadores de sustentabilidad en el cantón Mocache, provincia de los Ríos - Saltos Ibarra, Derian Enrique (2022)
The research was carried out in the Mocache canton, Los Ríos province, central tropical region of the Ecuadorian coast, with the objective of evaluating cattle farms through ecological, economic and sociocultural sustainability indicators. Five farms (cases) were selected, whose main characteristics were: availability and accessibility of the producer for data collection, and that the livestock component exists as the main activity within the production system. The study was of an observational, descriptive and exploratory type, the case study technique was used, applying surveys to each owner, as well as the observation of the property. Economic, ecological and socio-cultural indicators were available that allowed obtaining the General Sustainability Indicator